Revisiting the Tourism-Led Growth Hypothesis in a Dual Model Using Mwald Granger Causality Analysis - Yu-Chi, Sung (Asian Economic and Financial Review, 2018)
This study reinvestigates the tourism-led growth hypothesis in Taiwan by applying the Johansen co-integration and Modified Wald (MWALD) causality tests to long-term data-from 1958 to 2017. We employ both bivariate (international tourist arrivals and real GDP) and trivariate (international tourist arrivals, international tourist expenditures, and real GDP) models. We find that there is a long-run relationship between the three variables, and that there is a unidirectional Granger causality running from economic growth to international tourist arrivals in both bivariate and trivariate models, supporting the tourism-led growth hypothesis. In addition, the existence of bidirectional Granger causality between the real GDP and international tourist expenditures suggests that policymakers should relax regulations to increase tourism flows to promote economic growth.